Saberes docentes : constituição e mobilização dos saberes experienciais frente à inclusão em sala de aula de alunos com deficiência mental - Ferraz, Roselane Duarte (2008)
The constitution and mobilization process of teachers experiences with regard to inclusion in mentally deficient students classroom is analyzed. Research also investigates whether working experience with the above-mentioned children made any change in continuous training and in the constitution of the teacher s knowledge. Research, based on authors that discuss the epistemology of teachers practice and knowledge, was undertaken in a municipal government primary school in the urban area of the municipality of Itapetinga BA Brazil, in which the mentally deficient children were enrolled. Methodological options involved a qualitative approach and an ethnographical orientation due to the peculiarities of the investigation and its theoretical bases. Half-structured interviews with the teacher and the headmistress and observations in the classroom reported in a diary were used. Data revealed that the teacher appropriates herself with different types of knowledge when dealing with learning and teaching situations since daily school activities make possible the production and the mobilization of knowledge experiences. The teacher s practical knowledge acquires objectivity when subjective certainties are confronted with knowledge produced by the collective experience. Research showed that the teacher had her limitations when directing her pedagogical activities to mentally deficient children. Gaps hailing from initial training and from the school s organization and structure contributed towards difficulties experienced in her pedagogical proposals to attend to the mentally deficient students learning needs. The constitution and the mobilization process of teaching knowledge vis-à-vis mental deficiency involves aspects in professional training that do not merely depend on the articulation of experience knowledge with other types of knowledge, but also on the conditions of the school context. Consequently the continuation of the teacher s training is undertaken through team work.